Consumers’ acceptance toward local produced rice at Seri Mendapat, Jasin, Melaka / Ibrahim Salleh - Salleh, Ibrahim (Faculty Of Plantation And Agrotechnology, 2017)
Rice is the staple food for the local citizen in Malaysia. There are many factors affecting the consumers to buy and consume the local rice. To identify the factors, a study is conducted at the area of Seri Mendapat ,Jasin, Melaka. The objectives of this study are to find out the relationship between attributes that consumers consider when purchasing rice with the level of acceptance of consumer, to analyse level of consumer’s knowledge and to determine the consumer’s attitude toward local produced rice. The methodology that used in this study is survey method. Based on the result, it showed that there are relationships between acceptance of the consumers with the attributes that consumers consider when purchasing rice and level of the consumers knowledge toward local produced rice. From this study, I can conclude that the attributes of the local rice is the most influence factor in influencing them to buy. So, the local producers and suppliers need to study a lot about the attributes of rice in order to make their products are successfully accepted by the local markets and consumers.